2013
DOI: 10.1103/physrevlett.110.167001
|View full text |Cite
|
Sign up to set email alerts
|

Commensurability of the Spin-Density-Wave State of(TMTSF)PF62Observed byC

Abstract: A spin-density-wave (SDW) for (TMTSF)(2)PF(6) has been reported to appear below T(SDW) (=/~12 K), with a subphase transition at T* (=/~4 K). To determine the structure of the subphase, we synthesized (TMTSF)(2)PF(6), in which one side of the central carbon bond in each TMTSF molecule was replaced by (13)C, and utilized this compound in (13)C nuclear magnetic resonance measurements. Below T(SDW), the spectrum became broad and T(1)(-1) decreased, in agreement with previous results. Below T*, fine structures emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…From the 1/T 1 value, J/k B was estimated to be 112 K, which is in good agreement with the J/k B 98 K value evaluated from the magnetic susceptibility measurement. This result also supports the electronic state of this salt described by the dimer-Mott picture, according to which the localized spins interact with J, and the ground state of λ-(BEDT-TTF) 2 GaCl 4 is the AF ordered state rather than the SDW state due to the nesting of the Fermi surface observed in the TMTSF [TMTSF = tetramethyltetraselenafulvalene] system 23,24 . Because our result revealed that the ground state of λ-(BEDT-TTF) 2 GaCl 4 is the AF state, the insulating ground state adjacent to the SC phase in the phase diagram of λ-type salts is expected to be the AF insulating phase.…”
supporting
confidence: 78%
“…From the 1/T 1 value, J/k B was estimated to be 112 K, which is in good agreement with the J/k B 98 K value evaluated from the magnetic susceptibility measurement. This result also supports the electronic state of this salt described by the dimer-Mott picture, according to which the localized spins interact with J, and the ground state of λ-(BEDT-TTF) 2 GaCl 4 is the AF ordered state rather than the SDW state due to the nesting of the Fermi surface observed in the TMTSF [TMTSF = tetramethyltetraselenafulvalene] system 23,24 . Because our result revealed that the ground state of λ-(BEDT-TTF) 2 GaCl 4 is the AF state, the insulating ground state adjacent to the SC phase in the phase diagram of λ-type salts is expected to be the AF insulating phase.…”
supporting
confidence: 78%
“…The magnetic ground state of (TMTSF) 2 PF 6 undergoes also a sub-phase transition (T sub ) around 4 K below which there is coexistence between incommensurate and commensurate SDW modulations. [107] Interestingly, the 2k F and 4k F CDW modulations are no longer observed below T sub . [108][109] Thus, the vanishing of the charge modulation could be due either to a change of nature of the modulated state or to a drastic limitation of its spatial extend (inhomogeneous modulation [107] or glassy behavior [54]) affecting primarily the charge order.…”
Section: A Degrees Of Freedom Of the Anion Cavitymentioning
confidence: 97%
“…For the one-dimensional Bechgaard salt (TMTSF) 2 -PF 6 , for instance, several groups have established the low-temperature SDW phase next superconductivity [52][53][54][55]. X-ray scattering experiments revealed features associated with a CDW state even for temperatures below T SDW [56,57]; thus Clay, Mazumdar and collaborators concluded that charge and spin density waves coexist [58,59].…”
Section: B Interplay Of Broken Symmetry Ground States In Spin and Cha...mentioning
confidence: 99%